PERANCANGAN APLIKASI INVOICE BERBASIS MOBILE STUDI KASUS UMKM - Elmo Agusti (ARKA INSTITUTE, 2022)
Information technology plays an important role as a medium of information and communication in UMKM activities, one of which is the management of Angkringan stalls in the Pamulang area, South Tangerang. Based on this research activity, it is very useful for UMKM actors, namely through this mobile based invoice application, UMKM participants can view detailed sales reports without having to record every transaction manually. Through this mobile based invoice application, UMKM participants can print invoice via a bluetooth printer whitout manual writing, and this process can help the transaction management process more efficiently.